1990
DOI: 10.1111/j.1365-2958.1990.tb00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Constraints in chromosomal inversions in Escherichia coli are not explained by replication pausing at inverted terminator‐like sequences

Abstract: Regions close to the replication terminus of the Escherichia coli chromosome are strongly refractory to genomic inversions. Since these regions also harbour polar replication terminator-like sequences or pause sites, we have investigated the possibility that slowing of replication as a result of pausing at inverted pause sites is responsible for inability to isolate stable inversions affecting these regions. A mutation in the tus gene is known to abolish replication pausing at terminators. We show here that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Interestingly, and despite containing noninvertible segments [20][21][22][23], both S. typhimurium and E. coli mg1655 passed the uniformity test. The fit of uniformity in four pairwise comparisons is surprising for two additional reasons.…”
Section: Breakpoint Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, and despite containing noninvertible segments [20][21][22][23], both S. typhimurium and E. coli mg1655 passed the uniformity test. The fit of uniformity in four pairwise comparisons is surprising for two additional reasons.…”
Section: Breakpoint Distributionmentioning
confidence: 99%
“…Furthermore, we utilized MAGIC's results to analyze the breakpoint distribution in bacteria. Previous studies, on Salmonella typhimurium [20,21] and on Escherichia coli [22,23], have shown that they contain noninvertible (or nonpermissive) segments. For some of these segments, forcing an inversion by mechanisms different from those found in the cell resulted in organisms that are viable and that grow normally [24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some inversions of E. coli chromosomal regions are deleterious and induce an abnormal nucleoid structure [36,37] . The solenoidal model dictates that site position must be respected for full functionality.…”
Section: Explanatory Powermentioning
confidence: 99%
“…Extensive analysis in E. coli K12, selecting for inversions between homologous regions (such as Tn10s) inserted into the chromosome, has shown that many inversions in regions flanking TER are deleterious or not detected; these are called nondivisible zones (15). The region close to TER, including pyrC (b1062) to pyrF (b1281) (see Fig.…”
Section: Discussionmentioning
confidence: 99%